The Capital Structure as A Mediator Between Profitability and Company Size to Company Value in Textile And Garment Sector Companies Listed on The Indonesia Stock Exchange (IDX) - Zakina, Oky Fauzul; Ady, Sri Utami (Universitas Dr. Soetomo, 2023)
This study aimed to determine the effect of profitability and company size on company value with capital structure as an intervening variable in textile and garment sector companies listed on the Indonesia Stock Exchange (IDX) for 2018-2022. This research used a quantitative approach and secondary data from annual financial statements from www.idx.co.id. The population in this study was textile and garment sector companies listed on the Indonesia Stock Exchange (IDX) in the 2018-2022 period, with a population of 22 companies. Determining research samples used the purposive sampling method, and 18 companies with 90 data points were obtained as samples. Data analysis was performed using SEM-PLS version 3.0. The results of this study showed that profitability had a significant positive effect on capital structure. The size of the company had no impact on the capital structure. Profitability had a significant positive effect on the value of the company. The size of the company had no impact on the value of the company. Capital structure had a significant positive effect on the value of the company. Profitability had a significant positive impact on the value of the company with capital structure as an intervening variable; the size of the company did not affect the value of the company with capital structure as an intervening variable.